Psychometric properties of a scale to measure digital transformation perception in University students - González Gracia, Guadalupe; García López, Ramona Imelda; Cuevas Salazar, Omar (IE Revista de Investigación Educativa de la REDIECH, 2024)
The digital transformation originated in the industrial sector, but its influence has extended to the field of education. This variable has multiple approaches, as it was studied from different perspectives, both at macro and micro levels. Nevertheless, there is a void about which are the elements or dimensions related to this construct, thus efforts were made to measure it from different points of view. Therefore, the objective of this study was to determine the psychometric properties of the scale to measure the perception of university students on digital transformation. Quantitative research was conducted involving seven experts as judges and 349 undergraduate and graduate students participated. The results showed that it is a valid instrument (with evidence of content, construct and concurrent validity) composed of four dimensions: academic, linkage, technological and research; as well as reliable (McDonald’s Omega). These findings contribute information to the field of digital transformation in universities, as it is measured from the students’ perspective. Similarly, the results suggest that technology acceptance could influence the digital transformation process.